The science book of air - Ardley, Neil. (San Diego : Harcourt Brace Jovanovich, 1991)
Simple experiments demonstrate basic principles of air and flight.
"Gulliver books.".
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
4.7.
4.7
Keywords: Air -- Experiments -- Juvenile literature; Flight -- Experiments -- Juvenile literature; Air -- Experiments; Experiments; Flight -- Experiments; Air -- Experiments; Flight -- Experiments